Incipient plasticity in tungsten during nanoindentation: Dependence on surface roughness, probe radius and crystal orientation. (September 2018) - Beake, Ben D.; Goel, Saurav
Abstract: The influence of crystallographic orientation, contact size and surface roughness effects on incipient plasticity in tungsten were investigated by nanoindentation with indenters with a range of end radius (150, 350, 720 and 2800 nm) in single crystal samples with the (100) and (111) orientations. Results for the single crystals were compared to those for a reference polycrystalline tungsten sample tested under the same conditions. Surface roughness measurements showed that the R a surface roughness was around 2, 4, and 6 nm for the (100), (111) and polycrystalline samples respectively. A strong size effect was observed, with the stress for incipient plasticity increasing as the indenter radius decreased. The maximum shear stress approached the theoretical shear strength when W(100) was indented using the tip with the smallest radius. The higher roughness and greater dislocation density on the W(111) and polycrystalline samples contributed to yield occurring at lower stresses. Highlights: Stress for incipient plasticity on W increased with decreasing indenter radii. Maximum shear stress approached theoretical shear strength for W(100) indented by smallest radius indenter. Higher roughness and dislocation density on W(111) and polycrystalline samples contribute to yield at lower stresses